Integrated role of lifestyle habits in cardiometabolic risk factors according to sex in adolescents - Ana Paula Sehn; Caroline Brand; João Francisco de Castro Silveira; Roger Marshall; Jane Dagmar Pollo Renner; Cézane Priscila Reuter (Taylor & Francis Group, 2022)
Background A healthy lifestyle should be adopted by young people to maintain cardiometabolic health. Aim To verify the prevalence and the integrated role of lifestyle habits in cardiometabolic risk factors according to sex in adolescents. Subjects and methods Cross-sectional study developed with 1502 adolescents, aged 10-17 years. Lifestyle habits included physical activity, screen time and sleep duration evaluated through a questionnaire. Cardiometabolic risk score (CMRS) was calculated by summing z-scores, divided by 6. For statistical analyses, multivariable binary and multinomial logistic regression models were used. Results 80.7% of the boys classified with adverse CMRS presented physical inactivity, compared to normal CMRS. In girls, 42.6% showed inadequate sleep compared to normal CMRS. Boys classified as inactive showed higher odds for obesity, as well as altered triglycerides (TGs), and systolic blood pressure, risk for cardiorespiratory fitness (CRF), high waist circumference, and CMRS, compared to the active. A prolonged screen time increased the odds for altered glucose and decreased the odds for altered TGs. In girls, inadequate sleep duration presented higher odds for overweight, obesity, risk for CRF, and high CMRS, compared to adequate sleep. Conclusion Physical activity for boys and sleep duration for girls are important to maintain healthy metabolic health amongst youth.